RELASI KEPENTINGAN ELITE LOKAL DALAM PEMBANGUNAN GEOTERMAL (PLTP) DI DESA SOKORIA, KECAMATAN NDONA TIMUR, KABUPATEN ENDE - Rogerio Alvaro Roi Wangge; Ananias Riyoan Philip Jacob; Frans W. Muskanan (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The development of the Sokoria Geothermal Power Plant (GPP) in Sokoria Village, East Ndona Subdistrict, Ende Regency is part of Indonesia’s national renewable energy policy. However, this project is not only shaped by technical and economic considerations but also strongly influenced by local socio-political dynamics, particularly the interest relations of local elites. This study aims to analyze the forms of local elite interest relations in the development of the Sokoria GPP, the political, economic, and social interests underlying their involvement, and the impacts on local communities. This research employs a descriptive qualitative approach using in-depth interviews, field observations, and documentation as data collection methods. Data analysis is conducted using C. Wright Mills’ elite theory. The findings reveal that local elites play a dominant role in the decision-making process of the Sokoria GPP development, acting as intermediaries between developers and communities while also controlling information flows and benefit distribution. These interest relations tend to be elitist rather than participatory, resulting in unequal benefit distribution and community resistance. This study concludes that the success of geothermal development depends not only on technical and policy aspects but also on inclusive, transparent, and just socio-political governance.